A-maze-ing physics - Makhtar, N.; Abdullah, S. Z.; Aminy, N. N. K.; Puad, S. A. M. (2022)
Kinematics is one of the topics in physics that describes the motion of objects. Most of the students are getting confused to solve the problems of this topic since there are many considerations to take off before choosing and applying the equations. Creating game-based learning regarding this topic is a useful way to help the students understand this topic. This way is not just improving students' ability but allows the students to engage with educational materials playfully and dynamically. A-maze-ing Physics is game-based learning that uses Wordwall as a platform to create learning activities. This platform has fully customizable activities such as quizzes, word games, maze chases that can be used by the educator as an alternative way to review the students’ understanding with a quick revision. In this study, about 43 of the respondents from Pre-Science students have been selected to try the A-mazing-ing Physics game, and they have to give feedback on the game in a given survey form. Based on the feedback, the analysis showed that all the respondents agree that A-mazing-ing Physics is not just game based learning that helps them to more understanding about the kinematics but also attracts them to learn physics interactively.